Frontispiece: Structural color barcodes for biodiagnostics (View 2/2020). Issue 2 (26th June 2020) - Shang, Luoran; Wang, Yuetong; Cai, Lijun; Shu, Yilai; Zhao, Yuanjin
Abstract : In article number 8, Yuanjin Zhao, Yilai Shu, Luoran Shang and co‐workers demonstrate structural color barcodes with tailoring size, shape, structure, and bioactive moieties are finding extensive applications in the multiplex detection of disease‐specific biomarkers including at the molecular, subcellular, cellular, and organoids level, opening up new possibilities to the field of biodiagnostics.